2022
DOI: 10.1111/ejh.13810
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster prophylaxis with low‐dose acyclovir in patients with malignant lymphoma and multiple myeloma treated with autologous stem cell transplantation

Abstract: Background Herpes zoster (HZ) is a frequent complication after autologous stem cell transplantation (ASCT). The option of zoster prophylaxis with an antiviral drug is described in the literature, but there is no consensus on the drug and the dosage. Patients and Methods We analyzed the records of 310 patients treated with ASCT who were controlled regularly regarding HZ inter alia for at least 24 months following ASCT. Since 01/2015 patients received prophylactic low‐dose acyclovir (400 mg per day) during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Although it is suggested to use prophylactic for at least 6 months to 1 year after autologous transplantation in other hematological malignancies, 40,41 and more than half of the VZV reactivation occurred within 1 year of proteasome inhibitor initiation, 42 there is currently no consensus on how long patients should receive prophylactic medication when undergoing regimen other than transplant in patients with multiple myeloma. A recent study showed that HZ prophylaxis with low‐dose acyclovir over 12 months after ASCT is effective and well tolerated 43 . In our study, we demonstrate that prophylaxis should be administered until at least the end of one's treatment regimen.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Although it is suggested to use prophylactic for at least 6 months to 1 year after autologous transplantation in other hematological malignancies, 40,41 and more than half of the VZV reactivation occurred within 1 year of proteasome inhibitor initiation, 42 there is currently no consensus on how long patients should receive prophylactic medication when undergoing regimen other than transplant in patients with multiple myeloma. A recent study showed that HZ prophylaxis with low‐dose acyclovir over 12 months after ASCT is effective and well tolerated 43 . In our study, we demonstrate that prophylaxis should be administered until at least the end of one's treatment regimen.…”
Section: Discussionmentioning
confidence: 49%
“…A recent study showed that HZ prophylaxis with low‐dose acyclovir over 12 months after ASCT is effective and well tolerated. 43 In our study, we demonstrate that prophylaxis should be administered until at least the end of one's treatment regimen. Although further subgroup analysis did not show a significant different median duration between the two groups, we observed more scattered points beyond 1 year in the group without HZ infection.…”
Section: Discussionmentioning
confidence: 61%
“…In patients with chronic lymphocytic leukemia (CLL) treated with ibrutinib the incidence of HZ was 5% during a long-term follow-up while 2.9 cases per 1000 PY were documented in those treated with various regimens in the pre-ibrutinib era 24, 25 .…”
Section: Herpes Zoster Risk and Prevention In Lymphoproliferative Dis...mentioning
confidence: 99%
“…40 Abbasov E et al observed that administering low-dose acyclovir as a prophylactic measure against HZ was both effective and well-tolerated when extended beyond 12 months following autologous stem cell transplantation. 41 The ESCMID highlighted the potential for herpes zoster virus reactivation at any phase during bortezomib chemotherapy, advocating for the continuous use of acyclovir throughout the entire bortezomib treatment cycle. This approach was substantiated by the absence of herpes zoster reactivation post-completion of all bortezomib courses, indicating that extending acyclovir administration beyond the chemotherapy period may not be necessary.…”
mentioning
confidence: 99%